Cuba on the brink Castro, the missile crisis, and the Soviet collapse - Blight, James G. 1946-; Allyn, Bruce J.; Welch, David 1960- (Pantheon Books, 1993)
An account of a conference held in Havana in 1992, studying the causes and the course of the 1962 Cuban missile crisis, and revealing misperceptions on all sides that led to the brink of nuclear war.
Keywords: Außenpolitik; Cuban Missile Crisis, 1962 -- Congresses; Kubakrise; Cuba - Relaciones exteriores - Rusia; Cuba - Relaciones exteriores - Unión Soviética - Congresos, conferencias, etc; Rusia - Relaciones exteriores - Cuba; Unión Soviética - Relaciones exteriores - Cuba - Congresos, conferencias, etc; Sowjetunion; Cuba -- Foreign relations -- Soviet Union -- Congresses; Soviet Union -- Foreign relations -- Cuba -- Congresses; Konferenzschrift